EXPERIENCES OF ABILITY GROUPING (A CASE STUDY AT ENGLISH EDUCATION DEPARTMENT UIN ANTASARI) - Nani Hizriani; Saadillah Saadillah; Puji Sri Rahayu (LET: Linguistics, Literature and English Teaching Journal)
Ability grouping is a common educational practice which is intended to improve education quality by grouping students together according to their achievements.  This research focuses on the attitude and believes of the students and lecturers of English Education Department toward grouping ability in term of confidence, achievement, expectation, competition, cooperation and respect. This is a descriptive qualitative research since it is used to gain an understanding of underlying reasons, opinions, and motivations. The respondents of this research were students of academic year 2016, 2017 and 2018 and the lecturers. To collect the data, English proficiency test, questionnaires, and interview were used as the instruments. The findings from questionnaire and interviews mostly shows positive attitudes and believes toward ability grouping both from the students and the lecturers being investigated. There is little issue about respect experienced by some lecturers, yet, it is inconclusive. From the result, it is suggested that lecturers need to adjust materials, select appropriate techniques and methods to suit the students’ characteristics.